A experiência de implementação do sistema de ambiente colaborativo SISAC para a gestão de projetos em uma entidade pública - Homero Silva Junior (2009)
The preparation of projects and works related to buildings is becoming ever more complex given the involvement of various stakeholders and the substantial flow of information during the process. This process demands the replacement of the traditional (sequential) by thecollaborative. In this context, the use of the extranet or the collaborative environment system, SISAC, as a tool to aid in project management requires a different attitude from the professionals involved in its development. This work shows, through case studies the implementation of an extranet in the design of a public entity. The case studies cover threebuilding project procedures for room expansion of a police academy, a hospital facility and a post service to the community. From the methodological point of view, the analyses of the data are referenced in documents, interviews and observations. The research sought toexamine the degree of interaction among the specialties and project participants, study the management of communications and documentation of case studies, verify the particularities features found in the design process of the researched environment, and deploy the use ofinformation technology in the project management. The difficulties encountered in implementing the Extranet are pointed out from the acceptance of the project participants as to the use of the tool until the structure of environments in which they are inserted. The adaptation of the management process to the infrastructure characteristics of the researched environment provided for improvement of the collaborative environment with the inclusion of a function in the communication manager module. Based on the case studies, it was possible to evaluate the progress of the collaborative process and prepare a proposal forimplementation of the collaborative environment system, SISAC in the public and private agencies.